Jeřáb radiální portálový - Dias, Aleš (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2016)
Smyslem této diplomové práce je kompletní návrh radiálního portálového jeřábu, včetně důležitých pevnostních výpočtů dle norem a kontrola pomocí programu ANSYS Workbench. Maximální nosnost je 1 500 kg při délce vyložení ramene 12 000 mm a výšce zdvihu 3 600 mm. Jeřáb je řešen jako plně otočný a rozsah otáčení je tedy 360°. Práce obsahuje také výběr vhodného kladkostroje z katalogu výrobců včetně příslušenství, pojezdových kol, všech důležitých komponent a také MKP analýza konstrukce.

The aim of my thesis is a conceptual design radial gantry crane including the important strength calculations according to the standards and examinations by means of ANSYS Workbench. The lifting capacity is 1500 kg, the length of the boom is 12 000 mm and the height of lifting is 3600mm. The crane is designed as fully revolving and the angle turning is 360°. The work also includes the selection of a suitable lifting gear from the manufacturer´s catalogue including the accessories casters, all important components and also FEM construction analysis.
Radial gantry crane
Keywords: Radiální portálový jeřáb; portálový jeřáb; jeřáb; výložník; zdvihací ústrojí; ANSYS Workbench; MKP analýza; Radial gantry crane; gantry; crane; boom; lifting gear; ANSYS Workbench; FEM analysis